Polimorfismos nos genes DGAT-1 e A2M e suas associações com produção e qualidade do leite de búfalas da raça Murrah - Freitas, Ana Cláudia de [UNESP] (2014)
The search for genes that affect milk yield and composition traits has been the aim of many studies in recent years, as the case of candidate gene DGAT1, admittedly involved with the fat content in milk being of great interest to breeders of dairy herds. Another important gene, A2M, has association with cellular processes of the immune system, such as somatic cell count (SCC), directly linked to milk quality and animal health. The aim of the present study was to verify the existence of polymorphisms in this two genes and their effects in composition and milk yield traits in breed buffaloes (Bubalus bubalis). The sample was constituted by 200 buffaloes cows. Hair were used for the extraction of DNA. After PCR, the samples were analyzed by sequencing techniques. Were found six SNPs, but only three in the coding region, two in exon 17 of the DGAT1 gene (SNP 162G/A and 164C/T) and one in exon 29 of the gene A2M (SNP 241A/G ). The SNP 164C/T was associated with the characteristics fat percentage and protein percentage in milk at 5% significance, since the SNP 241A/G besides having association with the same characteristics, also presented with the characteristic fat production. Before addition, is supposed there may be some relation of this SNPs and characteristics of composition from milk like, production and percents of fat and protein in to the milk. Therefore, it can be completed these SNPs can be used as moleculars markers in MAS in buffaloes